Clinical and Pre-Clinical Evidence of Carbonic Anhydrase IX in Pancreatic Cancer and Its High Expression in Pre-Cancerous Lesions - Strapcova, Sabina (Cancers (Basel), 2020)
Hypoxia is a common phenomenon that occurs in most solid tumors. Regardless of tumor origin, the evolution of a hypoxia-adapted phenotype is critical for invasive cancer development. Pancreatic ductal adenocarcinoma is also characterized by hypoxia, desmoplasia, and the presence of necrosis, predicting poor outcome. Carbonic anhydrase IX (CAIX) is one of the most strict hypoxia regulated genes which plays a key role in the adaptation of cancer cells to hypoxia and acidosis. Here, we summarize clinical data showing that CAIX expression is associated with tumor necrosis, vascularization, expression of Frizzled-1, mucins, or proteins involved in glycolysis, and inevitably, poor prognosis of pancreatic cancer patients. We also describe the transcriptional regulation of CAIX in relation to signaling pathways activated in pancreatic cancers. A large part deals with the preclinical evidence supporting the relevance of CAIX in processes leading to the aggressive behavior of pancreatic tumors. Furthermore, we focus on CAIX occurrence in pre-cancerous lesions, and for the first time, we describe CAIX expression within intraductal papillary mucinous neoplasia. Our review concludes with a detailed account of clinical trials implicating that treatment consisting of conventionally used therapies combined with CAIX targeting could result in an improved anti-cancer response in pancreatic cancer patients.